Peran Pendidikan Multikultural di SMA Negeri 17 Samarinda dalam Menerapkan Sifat Toleransi Beragama - Dea Putri Wahdatul Adla; Kautsar Eka Wardhana; Imam Mustafa Syarif; Kiki Amelia; Norlita Norlita (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2020)
Education at this time is a tool for unifying the nation, equalizing opportunities, and developing one’s potential to the fullest. So that through education can minimaze the differences of all citizens so that they can develop their potential. This research is a type of qualitative research. The data analysis technique in this study uses the reception analysis method, namely by collecting data from in-depth interviews. This research is a descreptive study. The target in this study was students of SMA Negeri 17 Samarinda who were in grade 12. This research has analysis that qualitative narratives obtained from the rseults of interviews with profound, with students of SMA Negeri 17 Samarinda. The technique used in this study to collect data is by in-depth interviews which are then obtained qualitative narratives and analyzed to get answers to the formulations of this research problem. The conlusion that can be drawn from this study is that SMA Negeri 17 Samarinda has a very important role in the development of students ability to have insight, behavior to respond to the reality of an advanced and just life. The reality of live today is based on multicultural differences, the refore multicultural education can be said to be a process of developing all the potential or abilities of students who value pluarality and heterogenity as a consequence of religion, ethnicity, ethnicity and religion. So it can be concluded that multicultural education requires the highest respect and aprrection for human dignity and dignity from wherever He comes from and is to be relegius, especially in this environment of the SMA Negeri 17 Samarinda.